Thermal Analysis and Battery Life of Lithium-Ion 60 Volt / 23 Ah with Variation of Engine Rate on 3000 W Electric Motorcycle Prototype - Arif Devi Dwipayana; Ainul Ghurri; Suprapta Winaya (Asian Journal Science and Engineering, 2025)
Lithium-ion batteries in electric vehicles face challenges in terms of energy conversion efficiency and thermal resistance. One of the main factors affecting battery performance is the variation in engine speed, which has an impact on current consumption, voltage changes, and an increase in battery temperature. This study aims to comprehensively analyze the effect of engine speed variation on the electric current consumption, battery life, and thermal characteristics of a 60V/23Ah lithium-ion battery in a 3000W electric motorcycle prototype. In addition, this research also evaluates the durability of the battery under varying operational conditions to identify potential optimizations of the battery management system. The methods used in this research involved MATLAB-based experiments and simulations. Tests were conducted by measuring battery current, voltage, and temperature at six different engine speed levels, and then compared with simulation results developed using a mathematical model based on motor efficiency and battery internal resistance. The results show that an increase in engine speed is directly proportional to the current consumption and a decrease in battery voltage. In addition, the battery temperature increases steadily, with relatively small differences between experimental and simulation results. This research contributes to a better understanding of the energy dynamics of electric vehicle battery systems and offers a simulation model approach to optimizing the design of battery management systems. The results of this study can be used to improve energy conversion efficiency and extend battery life in electric vehicles. Further research can be conducted by considering more complex environmental parameters, such as cooling effects and vehicle dynamic load variations.